Length of stay, cost, and mortality of healthcare-acquired bloodstream infections in children and neonates: A systematic review and meta-analysis. (3rd March 2020) - Karagiannidou, Sofia; Triantafyllou, Christos; Zaoutis, Theoklis E.; Papaevangelou, Vassiliki; Maniadakis, Nikolaos; Kourlaba, Georgia
Abstract: Objective: To estimate the attributable mortality, length of stay (LOS), and healthcare cost of pediatric and neonatal healthcare-acquired bloodstream infections (HA-BSIs). Design: A systematic review and meta-analysis. Methods: A systematic search (January 2000–September 2018) was conducted in PubMed, Cochrane, and CINAHL databases. Reference lists of selected articles were screened to identify additional studies. Case–control or cohort studies were eligible for inclusion when full text was available in English and data for at least 1 of the following criteria were provided: attributable or excess LOS, healthcare cost, or mortality rate due to HA-BSI. Study quality was evaluated using the Critical Appraisal Skills Programme Tool (CASP). Study selection and quality assessment were conducted by 2 independent researchers, and a third researcher was consulted to resolve any disagreements. Fixed- or random-effect models, as appropriate, were used to synthesize data. Heterogeneity and publication bias were evaluated. Results: In total, 21 studies were included in the systematic review and 13 studies were included in the meta-analysis. Attributable mean LOS ranged between 4 and 27.8 days; healthcare cost ranged between $1, 642.16 and $160, 804 (2019 USD) per patient with HA-BSI; and mortality rate ranged between 1.43% and 24%. The pooled mean attributable hospital LOS was 16.91 days (95% confidence interval [CI], 13.70–20.11) and the pooled attributable mortality rate was 8% (95% CI, 6–9). A meta-analysis was not conducted for cost due to lack of eligible studies. Conclusions: Pediatric HA-BSIs have a significant impact on mortality, LOS, and healthcare cost, further highlighting the need for implementation of HA-BSI prevention strategies.